Development of drip irrigation system for sustainable agriculture / Muhammad Tajudin Mohmad Musa - Mohmad Musa, Muhammad Tajudin (Faculty of Plantation and Agrotechnology, 2019)
Irrigation can be defined as replenishment of soil water storage in plant root zone through methods other than natural precipitation. Irrigation is seen to have found its roots in the history of mankind since earliest beginning. It helps reduces the uncertainties, particularly the climatic uncertainties in agriculture practices. More water is used in the agriculture compare to other industry and certain area have difficulty to sustain the demand from the agriculture sector thus this will affect the industry to maintain agricultural sustainability. However, the irrigation method has a lot of diversity in their use in field such subsurface irrigation, drip system irrigation and many more. This study is conducted on the UiTM Jasin Share farm as to measure the moisture rate percentage of the soil in each irrigation point and to identify the suitable pattern in the agriculture field. The study is using the gravitational force as the power supply and the water source comes from the rain harvester. The study will show how the moisture in the soil will hold their water for the root’s uptakes and affecting their sustainability. The data is being recorded each week using the soil moisture meter in the time period of 5 weeks. The data will be collected in the morning (before) and the evening (after) drip irrigation. Based on the result, the drip irrigation system definitely saves more water and help to increase and retain soil moisture of plants thus gave more sustainability for the plant which in area that have problem with water resources can used this method as a way to handle with the problems.